Risk factors for complications in the post anesthesia period in elderly patients - Quispe Mendoza, Isabel Yovana; Giani Peniche, Aparecida de Cássia (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--> Objective. To identify the risk for complications in the post anesthesia recovery period in elderly patients. Methodology. Retrospective descriptive study. Data were collected from elderly patient’s medical records. Results. 110 patients were studied and had the following profile: male sex (56.4%, hypertensive (32.7%), and classified as ASA II (60.0%).With regard to the intraoperative: underwent abdominal surgery (53.6%), general anesthesia was given (50.9%), were in a supine position during the surgery (81.8%) and the intraoperative period was under three hours (62.7%). The most common complications were: Hypothermia (55.5%), pain (43.6%) and high blood pressure (36.4%). Conclusion. he preoperative visit importance to evaluate the risk factors that could influence in the surgical procedure was shown.